Numerical investigation into a surface plasmon resonance sensor based on optical fiber microring - Chunliu Zhao; Yanru Wang; Dongning Wang; Zhewen Ding (Photonic Sensors, 2017)
Abstract A reflective surface plasmon resonance (SPR) sensor based on optical fiber microring is proposed. In such a sensor, plasmons on the outer surface of the metallized channels containing analyte can be excited by a fundamental mode of a thin-core fiber (TCF). The refractive index (RI) sensing can be achieved as the surface plasmons are sensitive to changes in the refrective index of the analyte. Numerical simulation results show that the resonance spectrum shifts toward the shorter wavelength gradually when the analyte refractive index increases from 1.0 to 1.33, whereas it shifts toward the longer wavelength gradually when the analyte refractive index increases from 1.33 to 1.43, and there is a turning point at the refractive index value of 1.33. The highest sensitivity achieved is up to 2.30×103 nm/RIU near the refractive index value of 1.0. Such a compact sensor has potential in gaseous substance monitoring.